Personalized customization system solution using augmented reality technology - Feng, Liying; Ma, Liyao; Ng, Giap Weng (EDP Sciences, 2021)
This paper presents a personalized clothing customization system using Augmented Reality (AR) technology. The goal of this paper is creating a more interactive and immersive experience for tailor designer by bridging physical personalized clothing customization and digital resources. This system can make the traditional clothing customization process more convenient and efficient and has strong interaction and experience. At the same time, it reduces the time cost, labor cost and material cost of sample making in the traditional clothing customization process. This paper discusses the feasibility of the system, introduces the system development, testing, and application environment, the overall system design scheme and system workflow, and details the specific functions of each module. It also introduces the system detection methods and observation indicators. The system uses technologies such as augmented reality (AR) technology, Azure Kinect somatosensory technology, and OpenGL 3D rendering, combined with the functional advantages of the somatosensory virtual fitting system, focusing on the improvement and role of AR technology in the clothing customization process, effectively improving user satisfaction with clothing customization and saves production time and costs.